Developing Students' Speaking Ability Through Powerpoint Presentation - Imam Fauzi; Dian Hanifah (Loquen, 2018)
This research aimed to improve active learning through students’ PowerPoint presentations in the fisrt grade students of nursing class of Private Vocational High School Serang City 2015/2016 academic year. The method used was Classroom Action Research which consists of planning, acting, observing, and reflecting. The study was carried out in three cycles and the data of this study was gathered through: (1) Student’ presentations, (2) observations, and (3) students computer use survey. The results showed that there was improvement of active learning in the teaching and learning process of nursing class students. In the first cycle, 62,5% of 32 students performed their presentation poorly. Some causes, students were not familiar to practice oral presentation in English, 25% did their presentation satisfactorily and only 12,5% of them performed pretty good presentation in the classroom. After intensive classroom and practices, in cycle II explained that 40,63% students did their presentation poorly. 33,3% could present their topics satisfactorily and 28,13% students performed much better and some of them did their presentation with their better way. Cycle III revealed clearly that students speaking skills were getting better after they were given additional time for much practices on how to deliver a good presentation and operate computer program. It can be seen 21,8% students performed satisfactorally, 40,6% students presented their good performance, and 37,5% did their best performances in delivering English presentation. The application of PowerPoint presentation with the integration of media in computer program can engage Students interest in learning, motivate them to practice presentation orally and improve their speaking skills. In conclusion active learning through students’ PowerPoint presentations could increase the active teaching and learning process. Students also learned technology which is very helpful for their study and future career. This study, therefore, suggests that teachers consider this aid in teaching-learning processes.